2012
DOI: 10.1002/cvde.201106934
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of HfO2 Thin Films Employing a Heteroleptic Hafnium Precursor

Abstract: The application of a heteroleptic hafnium amide-guanidinate precursor for the deposition of HfO 2 thin films via a water-assisted atomic layer deposition (ALD) process is demonstrated for the first time. HfO 2 films are grown in the temperature range 100-300 8C using the compound [Hf(NMe 2 ) 2 (NMe 2 -Guan) 2 ] (1). This compound shows self-limiting ALD-type growth characteristics with growth rates of the order of 1.0-1.2 Å per cycle in the temperature range 100-225 8C. The saturation behavior and a linear dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
4
15
1
Order By: Relevance
“…In the present case, the leakage current is higher for the crystalline films (i. e., one decade higher than the polycrystalline one). These values are in a good agreement with HfO 2 films grown at temperatures as low as 150 • C [43]. The leakage current measured for the crystalline films could be due to the presence of grain boundaries which are not present in the amorphous layer [44][45][46].…”
Section: Resultssupporting
confidence: 81%
“…In the present case, the leakage current is higher for the crystalline films (i. e., one decade higher than the polycrystalline one). These values are in a good agreement with HfO 2 films grown at temperatures as low as 150 • C [43]. The leakage current measured for the crystalline films could be due to the presence of grain boundaries which are not present in the amorphous layer [44][45][46].…”
Section: Resultssupporting
confidence: 81%
“…The (Me 2 N) 2 Hf(guan‐NMe 2 ) 2 (bis(dimethylamido)‐bis(N,N(‐diisopropyl‐2‐dimethylamido‐guanidinato hafnium) precursor was evaluated for the ALD of HfO 2 thin films using water as the oxygen source. Self‐limiting growth was achieved at 200°C with a high GPC of 1.2 Å per cycle . A later study confirmed that self‐limiting growth was also taking place at 300°C with a saturative GPC of 0.8 Å per cycle, but did not provide any compositional analysis…”
Section: Ald Of Groups 4 and 5 Oxide Thin Filmsmentioning
confidence: 95%
“…The existence of an ALD temperature window is, however, neither indicative of nor necessary for a process to exhibit self‐limiting growth, but allows for a more robust process as small changes in the temperature do not affect the growth rate of the film. Wide ALD windows have been seen earlier in several other processes employing guanidinate precursors as well …”
Section: Resultsmentioning
confidence: 62%
“…In addition, many guanidinate complexes have good volatility and high thermal stability . So far, guanidinate compounds have been introduced as either homo‐ or heteroleptic ALD precursors in the deposition of high‐ k oxides (TiO 2 , ZrO 2 , HfO 2 , Gd 2 O 3 , Dy 2 O 3 ). In addition, they have been used in the metal‐organic (MO)CVD of rare‐earth oxides (Gd, Dy) as well as Gd, Ta, and W nitrides.…”
Section: Introductionmentioning
confidence: 99%